Visual Identity Development Concept on Promotion and Communication Media of Pacitan Vocational Community College: Konsep Pengembangan Identitas Visual Pada Media Promosi Dan Komunikasi Akademi Komunitas Negeri Pacitan (AKN Pacitan) - Ratih Prameswari, Citra; Abadi, Fajar; Indra Kumala, Charisma (Universitas Muhammadiyah Sidoarjo, 2024)
Previous research on designing a visual guidebook for AKN Pacitan continues in the current research. The visual identity of AKN Pacitan in accordance with the statutes has been packaged in a guidebook, which will later become a visual identity standard for all AKN Pacitan promotional and communication media. The website is one of the media for promotion and communication of AKN Pacitan to the wider community. The visual identity display and website layout are adjusted to those already in the visual guidebook. This research aims to ensure that the visual identity of AKN Pacitan can be implemented into all promotional and communication media of AKN Pacitan, especially for website media.